E-LEARNING SEBAGAI MEDIA PEMBELAJARAN DI MASA PANDEMI: (Studi Kasus: SMP AL-INAYAH) - Siti Yuliyanti; Doni Hermana (Jurnal Teknologi Informasi dan Komunikasi, 2021)
The world of education in Indonesia is experiencing a significant development. This development can be seen from the increasingly diverse learning methods used. The method used uses a lot of various media to improve the quality of learning outcomes. The development of various learning media is in line with the increasingly rapid technological advances. Thedynamics of today's technology achieve tremendous acceleration. The technology that was learned several years ago has begun to be replaced with new technology, including various conventional ways of learning. The form of information technology development that can be used as a learning medium is to use e-learning. E-learning is an innovation that can be used in the learning process, not only in the delivery of learning material but also changes in the abilities of various competences of  students. Through e-learning, students not only listen to material descriptions from educators but also actively observe, do, demonstrate, and so on. Teaching material can be virtualized in various formats so that it is more interesting and more dynamic so that it can motivate students to go further in the learning process.